If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -22 = 60 + 6x Reorder the terms: -22 + 8x = 60 + 6x Solving -22 + 8x = 60 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -22 + 8x + -6x = 60 + 6x + -6x Combine like terms: 8x + -6x = 2x -22 + 2x = 60 + 6x + -6x Combine like terms: 6x + -6x = 0 -22 + 2x = 60 + 0 -22 + 2x = 60 Add '22' to each side of the equation. -22 + 22 + 2x = 60 + 22 Combine like terms: -22 + 22 = 0 0 + 2x = 60 + 22 2x = 60 + 22 Combine like terms: 60 + 22 = 82 2x = 82 Divide each side by '2'. x = 41 Simplifying x = 41
| 7(a-6)+11=4(a-4) | | (3x^1)/(y^-1) | | -p^2-11p=0is | | 5-12x=-43 | | 34*m-1/3=1/2 | | f(x)=567 | | 3a^3+3ab^2+5a^2b+5b^3= | | 4+3n=6-5(n-2) | | 17-3n=27 | | -2m-2+m=-0.4(5m+20) | | 35/1000=x | | 4+b=-3(3b+2) | | 35=.5(3)(7+b) | | 1000-35=x | | 20-13=3x | | 11x+35=1000 | | -5h+2=-4(h-1) | | 1000x-35=x | | 1000-35x=x | | 21x=108 | | 35x+1000=x | | 104-(6x+4)=6(x+8)+x | | 4.5+2.5k=14.5+2k | | 15/16÷7/10 | | X^3+ax^2=0 | | 15/16/7/10 | | 40x+5(1.5x)=53000 | | -t^2(2t^4+4t-8)=0 | | 13+4t=4-5t | | q+18.30=20.00 | | 105-v=260 | | x*3+19=-170 |